Detection and longitudinal distribution of GW1516 and its metabolites in equine hair for doping control using liquid chromatography/high‐resolution mass spectrometry. (5th February 2021) - Ishii, Hideaki; Shibuya, Mariko; Leung, Gary Ngai‐Wa; Nozawa, Satoshi; Yamashita, Shozo; Yamada, Masayuki; Kushiro, Asuka; Kasashima, Yoshinori; Okada, Jun; Kawasaki, Kazumi; Kijima‐Suda, Isao
Abstract : Rationale: GW1516 is a peroxisome proliferator‐activated receptor‐δ (PPAR‐δ) agonist that is banned in horseracing and equestrian sports. Long‐term detection and longitudinal distribution of GW1516 in the mane of a horse are reported for the first time and this hair analysis could prolong the detection window of GW1516 for doping control. Methods: Mane hairs were divided into three segments (0–7, 7–15, and >15 cm from the cut end) and completely pulverized and homogenized for analysis. The pulverized hair samples were extracted with methanol followed by further purification and the extracts were analyzed by liquid chromatography/electrospray ionization high‐resolution mass spectrometry (LC/ESI‐HRMS) using a Q‐Exactive instrument. This method was successfully validated and applied to post‐administration samples to confirm the presence of GW1516 and its metabolites and estimate the uptake amounts of GW1516. Results: After administration of 150 mg of GW1516 to a thoroughbred mare, GW1516 was detected in one of two segments of all mane hairs, and four metabolites, namely GW1516 sulfoxide, GW1516 sulfone, 5‐(hydroxymethyl)‐4‐methyl‐2‐(4‐trifluoromethylphenyl)thiazole (HMTT), and 4‐methyl‐2‐[4‐(trifluoromethyl)phenyl]‐1, 3‐thiazole‐5‐carboxylic acid (MTTC), were also identified. The longitudinal distribution analysis results showed that the maximum uptake of GW1516 into hair (approximately 0.05 pg/mg) was observed at around 13 weeks post‐administration and GW1516 could be detected and confirmed up to 6 months post‐administration. Conclusions: The parent drug GW1516 was identified as the most appropriate monitoring target in equine hair for controlling its misuse in horses. The use of hair analysis could extend the detection time of GW1516 to at least 6 months after the administration of 150 mg of GW1516 to a thoroughbred mare.